2019
DOI: 10.15587/1729-4061.2019.175665
|View full text |Cite
|
Sign up to set email alerts
|

Development of an approach to using a style in software engineering

Abstract: Розроблено пiдхiд керованого онтологiєю застосування стилiв в iнженерiї програмного забезпечення. Сутнiсть пiдходу полягає у використаннi онтологiї не тiльки для представлення стилiв, но також для контролю застосування стилiв пiд час створення i супроводження програмного забезпечення. При цьому, для представлення стилю створюється вiдповiдна онтологiя та засоби пiдтримки розробника, а для контролю застосування стилю в робочих продуктах фаз життєвого циклу програмного забезпечення створюються засоби (ризонери) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 11 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…is relevant [50]. Technological skills imply ability to work with technology, it is necessary to define rational limits of requirements for personnel who will work with this technology [51]; coordination and step-by-step implementation of actions and operations aimed at achieving the desired result; the uniqueness and the regularity of the procedures and operations available in the technology.…”
Section: Organizational and Pedagogical Conditions For Training Higher Education Applicants By Learning Tools Of A Competence-oriented Enmentioning
confidence: 99%
“…is relevant [50]. Technological skills imply ability to work with technology, it is necessary to define rational limits of requirements for personnel who will work with this technology [51]; coordination and step-by-step implementation of actions and operations aimed at achieving the desired result; the uniqueness and the regularity of the procedures and operations available in the technology.…”
Section: Organizational and Pedagogical Conditions For Training Higher Education Applicants By Learning Tools Of A Competence-oriented Enmentioning
confidence: 99%
“…The analysis of scientific publications has shown that peculiarities of professional training of IT-specialists have been studied by O. Dubinina [4], A. Striuk [5], M. Sydorov [6], L. Tereminko [2] et al Researchers V. Kruhlyk [8], V. Osadchyi [9] have been engaged in the analysis of professional qualities of software engineers. Certain aspects of communicative training of IT-specialists have been investigated by H. Babii [10], Ya.…”
Section: Peculiarities Of Training For Itspecialists At Higher Educatmentioning
confidence: 99%
“…Therefore, it is advisable to conduct training within a software development company; involve professional developers in teaching disciplines; to organize practical classes according to modern requirements. Second, students should integrate their own knowledge and skills and direct the results to software development, and teachers, using appropriate teaching materials, should simplify this integration [6]. In their study, the authors have not focused on communicative training for future software engineering professionals.…”
Section: Peculiarities Of Training For Itspecialists At Higher Educatmentioning
confidence: 99%